Integrating writing into science through student-made field guides. (1st October 2016) - Gaither, Elizabeth; Scott, Catherine Marie
ABSTRACT: In our experience, providing students with opportunities to explore outdoors has benefited them greatly in appreciating the outdoors and learning more about the environment. Similarly, researchers recognize that participants of outdoor schoolyard instruction have a more significant increase in cognitive understanding of ecological science concepts compared to students of traditional instruction (Cronin-Jones2000 ; Eick2012 ). However, such experiences not only provide opportunities to gain scientific content knowledge but also help students develop their writing skills. In this article, we describe a fifth grade unit on writing schoolyard field guides and provide examples of ways that we see these concepts translating across grade levels and content areas.